CONTROLLINGLAMPANDFANBYUSINGGSMMODULE - Miss. Harsha Sarjerao Gadekar , Miss.NishaGahininathGadekar ,Miss.PrajaktaSajjanPhalake; Ms.Pawar S.V. (International Journal of Innovations in Engineering Research and Technology, 2022)
Now a day's every system is automated in order to face new challenges in the Present daysituation. Automated systems have less manual operations, so that the Flexibility, reliabilitiesare high and accurate. Hence every field prefers automated control Systems. Especially in thefield of electronics automated systems are doing better Performance. Probably the mostuseful thing to know about the global system for mobile Communication is that it is aninternational standard. If you travel in parts of world, GSM is only type of cellular serviceavailable. Instead of analog services, GSM was developed as a digital system using TDMAtechnology.Thegoaloftheprojectistodevelopasystem,whichusesMobiletechnologythat keeps control of the various units of the home appliances, which executes with respect to thesignal sent by the mobile. For utilization of appliances the new concept has been thought tomanage them remotely by using GSM, which enables the user to remotely control switchingof domestic appliances. Just by dialing keypad of remote telephone, from where we arecalling we can perform ON / OFF operation of the appliances. The ranges of appliances thatcan be controlled through tele remote systems are many in numbers. Some of them are asfollowsandthisdependsupontheusagepriorityoftheappliances i.e.,LightsSystemorotherelectrical/electronicappliances.